Evidence against an Essential Role of COPII-Mediated Cargo Transport to the Endoplasmic Reticulum-Golgi Intermediate Compartment in the Formation of the Primary Membrane of Vaccinia Virus - Husain, Matloob (American Society for Microbiology, 2003)
Vaccinia virus assembles two distinct lipoprotein membranes. The primary membrane contains nonglycosylated proteins, appears as crescents in the cytoplasm, and delimits immature and mature intracellular virions. The secondary or wrapping membrane contains glycoproteins, is derived from virus-modified trans-Golgi or endosomal cisternae, forms a loose coat around some intracellular mature virions, and becomes the envelope of extracellular virions. Although the mode of formation of the wrapping membrane is partially understood, we know less about the primary membrane. Recent reports posit that the primary membrane originates from the endoplasmic reticulum-Golgi intermediate compartment (ERGIC). According to this model, viral primary membrane proteins are cotranslationally inserted into the ER and accumulate in the ERGIC. To test the ERGIC model, we employed Sar1(H79G), a dominant negative form of the Sar1 protein, which is an essential component of coatomer protein II (COPII)-mediated cargo transport from the ER to the ERGIC and other post-ER compartments. Overexpression of Sar1(H79G) by transfection or by a novel recombinant vaccinia virus with an inducible Sar1(H79G) gene resulted in retention of ERGIC 53 in the ER but did not interfere with localization of viral primary membrane proteins in factory regions or with formation of viral crescent membranes and infectious intracellular mature virions. Wrapping of intracellular mature virions and formation of extracellular virions did not occur, however, because some proteins that are essential for the secondary membrane were retained in the ER as a consequence of Sar1(H79G) overexpression. Our data argue against an essential role of COPII-mediated cargo transport and the ERGIC in the formation of the viral primary membrane. Instead, viral membranes may be derived directly from the ER or by a novel mechanism.